1991
DOI: 10.1029/91ja00155
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of corotating stream fronts near the ecliptic plane in the inner solar system: 2. Three‐dimensional tilted‐dipole fronts

Abstract: We develop a numerical model that treats the three‐dimensional (3‐D) magnetohydrodynamic interactions taking place at interplanetary corotating stream fronts near the heliographic equator during those periods of the solar cycle when the large‐scale coronal magnetic structure is in the tilted‐dipole configuration. The dynamic simplicity of the tilted‐dipole geometry permits the formulation of a local approximation valid over a limited range of heliographic latitudes and longitudes centered about the stream fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
119
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(135 citation statements)
references
References 19 publications
13
119
0
3
Order By: Relevance
“…They found qualitative agreement with Gosling et al [1993] in that solar wind is deflected eastward and equatorward ahead of the CIR and westward and poleward behind the CIR. Clack et al [2000] also observed that a CIR from the Northern coronal hole had a Southern tilt out of the ecliptic, while a CIR from the Southern coronal hole had a Northern tilt out of the ecliptic, as predicted for a simple dipole model of coronal hole structure [Lee, 2000;Pizzo, 1991].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…They found qualitative agreement with Gosling et al [1993] in that solar wind is deflected eastward and equatorward ahead of the CIR and westward and poleward behind the CIR. Clack et al [2000] also observed that a CIR from the Northern coronal hole had a Southern tilt out of the ecliptic, while a CIR from the Southern coronal hole had a Northern tilt out of the ecliptic, as predicted for a simple dipole model of coronal hole structure [Lee, 2000;Pizzo, 1991].…”
Section: Introductionmentioning
confidence: 85%
“…Previous observational studies [Clack et al, 2000;Gosling et al, 1978Gosling et al, , 1993Riley et al, 1996] of CIRs' three dimensional structure used data from Ulysses. This paper for the first time studies the local three dimensional tilt of CIRs at 1 AU over an entire solar cycle and compares observations to the predictions of Lee [2000] and Pizzo [1991] regarding CIR formation, shape, and evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the basic structure had been predicted by global MHD simulations performed by Pizzo (1991). However, it was not until Ulysses measurements began to uncover a systematic picture of the properties of CIRs at mid latitudes during the declining phase of Solar Cycle 22, that these earlier numerical results began to be appreciated (Pizzo and Gosling, 1994).…”
Section: Corotating Interaction Regionsmentioning
confidence: 97%
“…These compression waves steepen and eventually form a shock pair in the forward and in the reverse direction. Increasingly sophisticated models of stream interfaces have been developed over the past decades, beginning from purely hydrodynamic models (Carovillano and Siscoe, 1969;Hundhausen, 1973;Pizzo, 1978) to models including the full set of MHD-equations in three dimensions (Pizzo, 1991). In about three quarters of cases, shocks are formed outside 1 AU, when the angle of the Parker spiral has become sufficiently oblique relative to the radial flow direction.…”
Section: Introductionmentioning
confidence: 99%